The Application of Ushul Fiqh Principles in the Works of Dr. Sa'd bin Nashir al-Shatsri - Abdul Basit; Fatur Fahrozi; Mujio Mujio; Imam Sucipto; Rizzaldy Satria Wiwaha (al-Afkar, Journal For Islamic Studies, 2026)
The global water crisis has become an urgent issue demanding responses from various disciplines, including Islamic law. Water wastage (israf al-ma’), as one of the contributors to this crisis, represents both an ethical-theological and ecological problem. This article aims to analyze the istinbat (legal derivation) methodology used to determine the ruling on water wastage, with a case study of the work of Dr. Sa'd bin Nashir asy-Syatsri. Using a qualitative content analysis method applied to the text “Application of the Principles of Ushul Fiqh to the Ruling on Israf (Excessiveness) in Water Usage,” this study maps the framework of Islamic jurisprudence in responding to the issue of excessive consumption. The results show that the establishment of the prohibition (tahrim) on water wastage is based on a solid argument, derived from 27 shar‘i evidences through the application of 13 ushul fiqh principles. These principles include dalalah lafziyyah (such as al-nahy yadullu ‘ala at-tahrim and al-wa‘id yadullu ‘ala at-tahrim), dalalah ma‘nawiyyah (such as mafhum muwafaqah and mafhum mukhalafah), as well as maqasid-based principles (such as ad-dawran ma‘al ‘illah and the prohibition of violating collective rights). This study affirms that ushul fiqh possesses a rich methodological capacity to provide normative foundations for addressing contemporary ecological challenges.